The investigation and comparison of respiratory volumes in patients with chronic low back pain and healthy subjects - Shohreh Taghizadeh; Soraya Piroozi; Siyamand Mohammad Shahi; Hoda Najafi; Farahnaz Ghafari Nejad (Vesnu Publications, 2012)
Introduction: Besides having major effects on the stability of lumbar vertebrae, Diaphragm and abdominal muscles play an important role in respiration. The function of these muscles may gradually change in patients with chronic low back pain leading to an inefficacious respiration. The aim of this study was to evaluate respiratory volumes in a group of patients with chronic low back pain and to compare these volumes with those of healthy subjects. Materials and Methods: Eighty subjects were recruited in this case-control study. Respiratory volumes were measured in 40 patients with chronic low back pain and in 40 sex- and age-matched healthy control subjects. Data on pain severity, previous physiotherapeutic intervention, duration of pain, was recorded. The respiratory volumes were measured by a spirometer. The t test was used for statistical analysis. Results: The results showed that subjects in the case group had lower VC (in), VC (ex), FVC, FEV1, and F1V1 values than those in the control group (P £ 0.5). The two groups had no significant difference in terms of FEF 25%, FEF 50%, FEF 75%, PEF, PIF, and MEF (P > 0.5). Conclusion: A tendency toward altered contration in the diaphragm and abdominal muscles of patients with chronic low back pain may gradually result in muscle weakness and a changed respiratory pattern. Keywords: Diaphragm, Abdominal muscles, Low back pain, Respiratory volumes